MicroRNA‐192‐5p inhibits migration of triple negative breast cancer cells and directly regulates Rho GTPase activating protein 19. Issue 11 (6th August 2021) - Vajen, Beate; Greiwe, Luisa; Schäffer, Vera; Eilers, Marlies; Huge, Nicole; Stalke, Amelie; Schlegelberger, Brigitte; Illig, Thomas; Skawran, Britta
Abstract: Among the different breast cancer subtypes, triple‐negative breast cancer (TNBC) is associated with a poor prognosis, low survival rates, and high expression of histone deacetylases. Treatment with histone deacetylase inhibitor trichostatin A (TSA) leads to an increased expression of potential tumor‐suppressive miRNAs. Characterization of these miRNAs can help to find new molecular targets for treatment of TNBC. We identified differentially expressed miRNAs by microarray analyses after treatment with TSA in the TNBC cell lines HCC38, HCC1395, and HCC1935. The gene locus of hsa‐miRNA‐192‐5p (miR‐192) and hsa‐miR‐194‐2 (miR‐194‐2) with its host gene, long noncoding RNA miR‐194‐2HG, has been linked to inhibition of migration in different tumor types. Therefore, we examined tumor‐relevant functional effects using WST‐1‐based proliferation, capsase‐3/7‐based apoptosis, and trans‐well migration assays after transfection with miRNA mimics or specific siRNAs. We demonstrated the tumor‐suppressive capacity of miR‐192 in TNBC cells, which was exerted through inhibition of proliferation, induction of apoptosis, and reduction of migration. Gene expression and bioinformatics analyses of TNBC cell lines transfected with miR‐192 mimics, identified a number of genes involved in migration including the Rho GTPase Activating Protein ARHGAP19. Through RNA immunoprecipitation we demonstrated the direct binding of miR‐192 and ARHGAP19 . Downregulation of ARHGAP19 expression by either miR‐192 or siRNA inhibited migration of TNBC cells significantly. Our findings demonstrate that overexpression of epigenetically deregulated miR‐192 decreases proliferation, promotes apoptosis, and inhibits migration of TNBC cell lines.